Governing Taiwan and Tibet : democratic approaches - He, Baogang, 1957- (Edinburgh University Press, 2015)
Problematises China's current policies towards Tibet and Taiwan and offers a fresh democratic approach. When it comes to talking about democracy in China, Chinese nationalists argue that it cannot solve China's problems, while Chinese liberals remain unduly silenced. But China is facing a national identity crisis, compounded by Tibet and Taiwan, where significant proportions of both populations do not identify with the Chinese nation-state. Could democracy realistically address the problems in China's national identity? Baogang He opens up a dialogue in which Chinese liberals can offer viable alternatives in defence of key democratic principles and governance. He upholds the search for a political space in which democratic governance in China can feasibly be developed. Problematises existing hard-liners' realist policies towards Tibet and Taiwan by examining how democracy can or cannot provide an answer Examines the different meanings, practices, institutions and various impacts of democracy with regards to the problem of China's national identity Presents the difficulties and obstacles to the democratic approach to the respective Tibet and Taiwan questions